Components and Analysis Method of Enterprise Resource Planning (ERP) Requirements in Small and Medium Enterprises (SMEs) - Yousef Khaleel; Anmar Abuhamdah; Mutaz Abu Sara; Bassam Al-Tamimi (Institute of Advanced Engineering and Science, 2016)
With the fast development of information technologies and enterprise software, Enterprise Resource Planning (ERP) systems are increasingly adopted by more small and medium enterprises (SMEs). Based on this trend, it is necessary to develop ERP systems in a manner that meets and fits the SMEs requirements and needs. This paper proposes conceptual components of ERP requirements that are required for generating ERP system functions. In addition, it proposes an ERP requirements analysis method for ERP system developments in order to produce the proper ERP system functions for SMEs. The advantage of this analysis method is that it is easy to analyze and integrate the special requirements of the ERP development for distinguishing a sub-sector of SMEs. In this paper, by analyzing the components of requirements and the relationship of the business process modelling, several basic concepts are given and the method of the process analysis and modelling is also expressed.